Adaptive turbo coded OFDM - Haider, S.A.; Noori, K. (Journal of Digital Information Management, 2007)
In this paper the system throughput of an OFDM system is enhanced by adding turbo coding and adaptive modulation (AD). Simulation is done over a time varying Raleigh fading channel. Each OFDM block is individually modulated according to channel state information acquired during the previous burst. The system automatically switches from higher to lower order modulation in order to maintain a constant bit error rate. Turbo codes are added for forward error correction, in addition to adaptive modulation. The end goal is to increase the system throughput while maintaining a bit error rate (BER) of 10-2.
Keywords: Adaptive modulation; OFDM; Turbo coding

A layered MIMO OFDM system with channel equalization - Noori, K.; Haider, S.A. (Journal of Digital Information Management, 2007)
This paper proposes a simple and efficient method for layered MIMO-OFDM system with channel equalization. Temporal variations in the channel are due to Doppler spread, a sign of relative motion between transmitter and receiver. Results are simulated in both Rayleigh channel and additive white Gaussian noise (AWGN) channel. Decision feedback equalizer (DFE) with recursive least square (RLS) algonthm is used for channel equalization. Different type of Layered structure is applied to MIMO-OFDM system and their performance is evaluated. Different modulations schemes are used with same number of transmit and receive antennas. Simulation results are shown for both vertical and horizontal coded layered structure MIMO-OFDM systems with different modulation schemes and different number of transmit antennas.
Keywords: Graphsdecomposition algorithm; VDM; Vienna development method